Karakteristik Kimia dan Organoleptik Sabun Padat Dengan Penambahan Serbuk Daun Ketepeng Cina (Cassia alata L.) - Eko Rifkowaty, Encik; Nopriyanti, Marisa; Kholil, Munawar; Novitasari, Dhea; Septiana, Emi (Politeknik Negeri Ketapang, 2023)
The raw material for making solid soap in this research was coconut oil which was then added with ketepeng leaf powder. The purpose of adding ketepeng leaf powder to soap is easy to use of ketepeng leaves as a skin medicine. Ketepeng leaves have the function of treating skin diseases because its contain secondary metabolite compounds. The treatment in this study consisted of three variations were the addition of 2, 4 and 6 grams of ketepeng leaf powder. The organoleptic characteristics tested in this research were color, aroma, amount of foam, and irritation test, while chemical characteristics included hardness level, water content, pH, and free alkali. Based on the research results, it is known that solid soap with the addition of ketepeng leaf powder meets the quality requirements of the Indonesian National Standard for solid bath soap based on the parameters of water content, pH and free alkali, and does not cause irritation. The color parameters and amount of foam in the 2 gram treatment were significantly different from the other two treatments, while the aroma parameters were not significantly different between the three treatments.